The Effectiveness of Herbal Antibacterial Formulations Against Mastitis-Causing Bacteria in Dairy Cattle - Sari Suryanah; Syifa Nurjannah (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2021)
This study aimed to determine the effectiveness of antibacterial formulations derived from herbal plants against mastitis-causing bacteria in dairy cattle. Herbal extracts composed of betel leaves extract, kecombrang flower extract, and turmeric extract were tested against Staphylococcus aureus, Streptococcus agalactiae, and Escherichia coli. The research was carried out in a Completely Randomized Design (CRD) using ten treatments and four replications at the Laboratory of Research and Testing, Faculty of Animal Husbandry, Padjadjaran University. The results showed that herbal antibacterial formulations could inhibit the growth of Staphylococcus aureus, Streptococcus agalactiae, and Escherichia coli bacteria. The most inhibitory power was obtained from P8 treatment (50% betel leaves + 50% kecombrang flower + 50% turmeric) categorized in